2020
DOI: 10.1101/2020.05.11.088674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid isolation of potent SARS-CoV-2 neutralizing antibodies and protection in a small animal model

Abstract: The development of countermeasures to prevent and treat COVID-19 is a global health priority. In under 7 weeks, we enrolled a cohort of SARS-CoV-2-recovered participants, developed neutralization assays to interrogate serum and monoclonal antibody responses, adapted our high throughput antibody isolation, production and characterization pipeline to rapidly screen over 1000 antigen-specific antibodies, and established an animal model to test protection. We report multiple highly potent neutralizing antibodies (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
157
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(171 citation statements)
references
References 15 publications
13
157
0
1
Order By: Relevance
“…Of 294 RBD-targeting antibodies, 10% are encoded by IGHV3-53, as compared to only 0.5% to 2.6% in the repertoire of naïve healthy individuals ( 29 ) with a mean of 1.8% ( 30 ). The prevalence of IGHV3-53 in the antibody response in SARS-CoV-2 patients has also been recognized in some recent antibody studies ( 20, 22, 27 ). These observations indicate that IGHV3-53 represents a frequent and public antibody response to the SARS-CoV-2 RBD.…”
Section: Mainmentioning
confidence: 66%
See 2 more Smart Citations
“…Of 294 RBD-targeting antibodies, 10% are encoded by IGHV3-53, as compared to only 0.5% to 2.6% in the repertoire of naïve healthy individuals ( 29 ) with a mean of 1.8% ( 30 ). The prevalence of IGHV3-53 in the antibody response in SARS-CoV-2 patients has also been recognized in some recent antibody studies ( 20, 22, 27 ). These observations indicate that IGHV3-53 represents a frequent and public antibody response to the SARS-CoV-2 RBD.…”
Section: Mainmentioning
confidence: 66%
“…To understand the molecular features that endow IGHV3-53 with the ability to act as a public antibody, we determined crystal structures of two IGHV3-53 neutralizing antibodies, namely CC12.1 and CC12.3, in complex with the SARS CoV-2 RBD and also in the presence of the SARS-CoV1/2 cross-reactive Fab CR3022 ( 17 ). CC12.1 and CC12.3 were previously isolated from a SARS-CoV-2-infected patient and shown to be SARS-CoV-2 RBD-specific ( 27 ). Although CC12.1 and CC12.3 are both encoded by IGHV3-53, CC12.1 utilizes IGHJ6, IGKV1-9, and IGKJ3, whereas CC12.3 utilizes IGHJ4, IGKV3-20, and IGKJ1.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…were over-represented . Other studies have also reported anti-SARS-CoV-2 mAbs derived from these genes (Brouwer et al, 2020;Cao et al, 2020;Chi et al, 2020;Ju et al, 2020;Rogers et al, 2020;Seydoux et al, 2020;Wu et al, 2020c;Zost et al, 2020).…”
Section: A Cryo-em Structure Of a Monoclonal Fab-s Protein Complex Rementioning
confidence: 96%
“…The SARS-CoV spike proteins are known targets of protective immunity, eliciting both neutralizing antibodies and T-cell responses upon natural infection 8 . Consequently, the spike protein is a primary target for SARS-CoV-2 vaccine development, with emphasis on the receptor-binding domain (RBD), which appears to be the target for most neutralizing antibodies [9][10][11][12][13][14][15] . The urgent need of an effective SARS-CoV-2 vaccine, to contain the worldwide pandemic and prevent new viral outbreaks, has led to a global effort involving a wide range of vaccine technologies.…”
Section: Introductionmentioning
confidence: 99%